A Flexible Polyphosphate‐Driven Regeneration System for Coenzyme A Dependent Catalysis. Issue 22 (16th October 2017) - Mordhorst, Silja; Maurer, Alice; Popadić, Désirée; Brech, Johanna; Andexer, Jennifer N.
Abstract: Coenzyme A (CoA) is a common cofactor in biochemical reactions, and CoA‐dependent enzymes catalyze essential steps in anabolism and catabolism. This complex molecule also plays an important role in the synthesis of many high‐value products, such as synthetic antibiotics, vitamins, pheromones, and biopolymers. Nevertheless, the synthetic potential for biocatalytic processes cannot be fully exploited owing to the lack of an efficient regeneration system. Here, we report an acyl‐CoA regeneration system with integrated adenosine triphosphate (ATP) regeneration that is based on inexpensive polyphosphate as the single energy source. In the four‐enzyme cascade, two cofactors, acyl‐CoA and ATP, are each regenerated up to 2000 times. The applicability for different acyl donors and acceptors is shown by HPLC analysis. Owing to its flexibility toward virtually all relevant substrates, the system has the potential to make CoA‐dependent reactions more accessible for chemical synthesis in vitro. Abstract : Two in one : Inexpensive and stable polyphosphate fuels a four‐enzyme cascade for the application of acyl‐coenzyme A (acyl‐CoA)‐dependent transferases by using a broad range of acyl donors and acceptors. The two cofactors required in this system, acyl‐CoA and adenosine triphosphate (ATP), are regenerated by using carboxylate‐CoA ligases and polyphosphate kinases.